Mania as a Result of Using Disulfiram at the Prescribed Amount During the Fifth Month of Maintenance Therapy: A Case Report - Yağcı, İbrahim and İnaltekin, Ali (Addicta: The Turkish Journal on Addictions, 2023)
Disulfiram is a medication that raises blood acetaldehyde levels by inhibiting aldehyde dehydrogenase. It has been reported that taking disulfiram can cause psychosis or mania. There are only a few case reports about mania in the literature. We introduce this case of disulfiram-induced mania without dose adjustment, whereas continuing maintenance alcohol addiction treatment with disulfiram at the prescribed amount in a patient with no psychiatric history. Mr KA, a 57-year old patient with a history of 25 years of alcohol consumption, had stopped drinking 5 months ago and had been taking disulfiram (500 mg/day) for 5 months. During treatment, he was admitted to the outpatient clinic with complaints of decreased need for sleep, increased speech, and psychomotor activity, in particular for 4–5 days. During the psychiatric examination, it was discovered that the rate of speech had increased, that flight of ideas was present, and that the affect was cheerful and nervous. There was an increase in self-esteem and grandiose delusion. The examination revealed psychomotor agitation. The patient was admitted to the hospital for examination, follow-up, and treatment. Mania was observed. Treatment with valproate 1000 mg/day and risperidone 4 mg/day was planned. The patient showed no psychotic or manic symptoms while continuing outpatient clinic controls. Rare complications, such as manic episodes, might occur even in patients receiving the prescribed amount and long-term disulfiram treatment.